Flexible graphite bipolar plate micropore plugging agent
By using a combination of microporous plugging agent of epoxy cyclohexylethylcyclotetrasiloxane and high Tg methacrylate monomer in flexible graphite bipolar plates, the plugging agent in the prior art is solved at high temperature and B in the prior art. The problem of insufficient dissolution and bending strength in aqueous diol solution achieves high heat resistance and ethylene glycol resistance, and improves the long-term stability of hydrogen fuel cells.
Patent Information
- Application Number
- CN202411326021.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The microporous plugging agent of existing flexible graphite bipolar plates is prone to dissolve and generate holes and cracks in long-term high temperature and aqueous glycol solutions, resulting in gas leakage and reduced bending strength, making it difficult to meet the high-temperature operation requirements of hydrogen fuel cell vehicles.
20 to 40 parts by weight of epoxycyclohexylethylcyclotetrasiloxane (meth)acrylate ring-opening compound and 60 to 80 parts by weight of high Tg methacrylate monomer, combined with 0.5 to 2 parts by weight of flow The flat agent and 0.2 to 1.0 parts by weight of the radical thermal initiator are formed by a micropore plugging agent with high heat resistance and ethylene glycol resistance through epoxy ring-opening esterification reaction and radical thermal curing.
The airtightness and bending strength of flexible graphite bipolar plates at high temperatures are achieved, dissolution and cracks in aqueous ethylene glycol solution are avoided, and the long-term stability and heat resistance of the fuel cell are significantly improved.
Smart Images

Figure BDA0005055442850000021 
Figure BDA0005055442850000022 
Figure BDA0005055442850000051
Abstract
Description
Technical Field
[0001] The invention belongs to the field of hydrogen fuel cells, and in particular relates to a thermally cured microporous plugging agent for a flexible graphite bipolar plate of a hydrogen fuel cell stack. Background Art
[0002] Fuel cell bipolar plates are the core structural support components of hydrogen fuel cell stacks, and are divided into metal bipolar plates and graphite bipolar plates. Graphite bipolar plates are widely used in commercial vehicle fuel cell stacks because of their easy availability of raw materials, low cost, good chemical corrosion resistance, and long life. However, the flexible graphite plate itself has a microporous structure and must be impregnated with a plugging agent to ensure the airtightness of the bipolar plate. At the same time, after the plugging agent is cured, the flexible graphite plate must be given sufficient mechanical strength, chemical resistance (mainly ethylene glycol resistance) and long-term heat resistance.
[0003] Flexible graphite bipolar plates generally use (meth) acrylate monomers to compound into impregnated resin liquid as plugging agent (refer to Chinese patent CN 107706430B). Free radical thermal initiator is added before use, and the flexible graphite plate is impregnated in the plugging agent, and vacuum or pressure impregnation is performed to allow the plugging agent molecules to penetrate into the micropores of the flexible graphite bipolar plate, and then the plugging agent remaining on the surface of the bipolar plate is cleaned to prevent the plugging agent from affecting the conductivity of graphite after curing on the surface of the bipolar plate. The bipolar plate is then heated and cured in a water bath, and the plugging agent forms a dense network structure after curing, thereby giving the bipolar plate air tightness, compressive strength, chemical resistance and heat resistance.
[0004] After the flexible graphite bipolar plates are assembled into a fuel cell stack, they will be in contact with an ethylene glycol aqueous solution cooling medium at a temperature of 80 to 95°C for a long time during the operation of the fuel cell. They need to have resistance to the long-term high temperature of the ethylene glycol aqueous solution. (Meth)acrylate polymers have a certain solubility in ethylene glycol. As a result, after the fuel cell has been running for a long time, the bipolar plate plugging agent is partially dissolved in ethylene glycol, resulting in holes and cracks, which lead to gas leakage and failure.
[0005] In addition, the Tg of the methacrylate polymer or copolymer mentioned in Chinese patent CN 107706430B is relatively low, and there are few components with a Tg exceeding 100°C. The Tg of the long-chain alkyl acrylate polymer is even lower than zero degrees, and it is in a rubbery state at the operating temperature of the fuel cell. The bending strength of the graphite bipolar plate is greatly reduced, and it is difficult to meet the stringent requirements of hydrogen fuel cell vehicles for stable operation under long-term high temperatures. Summary of the invention
[0006] The purpose of the present invention is to provide a flexible graphite bipolar plate micropore plugging agent with good heat resistance and ethylene glycol resistance.
[0007] The technical solution to achieve the purpose of the present invention is:
[0008] In the first aspect, the present invention provides a flexible graphite bipolar plate micropore plugging agent with good heat resistance and ethylene glycol resistance, comprising: 20 to 40 parts by weight of a (meth) acrylated ring-opening compound of epoxycyclohexylethylcyclotetrasiloxane and 60 to 80 parts by weight of a high Tg methacrylate monomer, the total of the two being 100 parts by weight, as well as 0.5 to 2 parts by weight of a leveling agent and 0.2 to 1.0 parts by weight of a free radical thermal initiator.
[0009] Preferably, the (meth)acrylated ring-opening compound of epoxycyclohexylethylcyclotetrasiloxane has the following structure:
[0010]
[0011] Here, R represents a methyl group or a hydrogen atom.
[0012] Preferably, the (meth) acrylic acid esterified ring-opening compound of epoxycyclohexylethylcyclotetrasiloxane is prepared by reacting epoxycyclohexylethylcyclotetrasiloxane of formula I with acrylic acid or methacrylic acid in the presence of a catalyst to undergo an epoxy ring-opening esterification reaction:
[0013]
[0014] Specifically, the catalyst used for the epoxy ring-opening esterification reaction of acrylic acid or methacrylic acid includes: tertiary amines, quaternary ammonium salts, commonly used triethylamine, N,N-dimethylbenzylamine, N,N-dimethylaniline, trimethylbenzylammonium chloride, triphenylphosphine, triphenylantimony, chromium acetylacetonate, chromium isooctanoate, organic tin compounds, tetraethylammonium bromide, etc., and the amount used is 0.1% to 3% of the total mass of the reactants.
[0015] Specifically, in order to ensure that the epoxy ring-opening esterification reaction is complete, the amount of acrylic acid or methacrylic acid added should generally be 1.1 to 1.5 times the molar number of epoxy groups in epoxycyclohexylethylcyclotetrasiloxane.
[0016] Specifically, in order to prevent the self-polymerization of acrylic acid or methacrylic acid during the epoxy ring-opening esterification reaction, a small amount of free radical inhibitor can be added. Commonly used free radical inhibitors are any one of p-methoxyphenol (MEHQ), hydroquinone, 2,5-dimethylhydroquinone, 2,6-di-tert-butyl-4-methylphenol (BHT), etc. The amount of free radical inhibitor added is 0.01% to 1% of the total mass of the reactants.
[0017] Specifically, the epoxy ring-opening esterification reaction is an exothermic reaction, so it is very important to control the temperature in the initial stage of the reaction. Usually, epoxy cyclohexylethyl cyclotetrasiloxane is heated to 80-90°C, and acrylic acid or methacrylic acid, a catalyst and a free radical inhibitor mixture are added dropwise. After the addition is completed, the reaction temperature is controlled to 110-120°C and maintained at this temperature for 5 hours. The heating is stopped and the temperature is cooled to room temperature to obtain the target product.
[0018] Preferably, the high Tg methacrylate monomer is selected from any one of isobornyl (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, benzyl (meth)acrylate, phenyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, tetrahydrofuranyl methacrylate, tricyclodecyl (meth)acrylate, dicyclopentadiene (meth)acrylate, (meth)acryloylmorpholine and N,N-dimethylacrylamide, etc. Based on comprehensive considerations such as heat resistance and low viscosity, isobornyl (meth)acrylate, dicyclopentadiene (meth)acrylate or tricyclodecyl methacrylate is preferred.
[0019] Preferably, the leveling agent can be any leveling agent that has a wetting effect on the flexible graphite bipolar plate, and can be determined according to the impregnation amount of the plugging agent after the flexible graphite bipolar plate is wetting. The higher the impregnation amount, the better the effect of the leveling agent. German BYK leveling agents BYK-333 and BYK-3505, and three positive polymer superdispersants such as CH-1, CH-2, CH-3, CH-5, CH-6, CH-7, CH-8, CH-9, etc. are preferred.
[0020] Preferably, the free radical thermal initiator is an initiator with a decomposition temperature of 80 to 95° C., and an azo or peroxide free radical thermal initiator is selected. Free radical thermal initiators such as azobisisobutyronitrile, azobisisoheptanenitrile or benzoyl peroxide are preferred.
[0021] Preferably, various antioxidants, anti-aging agents, fluorescent agents, etc. may be added to the above composition based on considerations of weather resistance, heat resistance, and fluorescent recognition.
[0022] Compared with the prior art, the advantages of the present invention are:
[0023] (1) One of the components of the flexible graphite bipolar plate plugging agent of the present invention is the (meth)acrylated ring-opening compound of epoxycyclohexylethylcyclotetrasiloxane. Due to the hydrophobic and oleophobic properties and low surface tension of the organic siloxane structure, it has excellent ethylene glycol resistance and will not swell or dissolve when in contact with ethylene glycol aqueous solution under long-term high temperature. It is particularly suitable for plugging micropores in flexible graphite bipolar plates of hydrogen fuel cells.
[0024] (2) One of the components of the flexible graphite bipolar plate plugging agent of the present invention is the (meth)acrylated ring-opening compound of epoxycyclohexylethylcyclotetrasiloxane, each molecule of which contains 4 (meth)acryloyloxy groups that can be free radical polymerized. After copolymerization with a high Tg methacrylate monomer, it has high heat resistance, low curing shrinkage, and small residual stress, which is beneficial for the bipolar plate to maintain good bending strength at high temperatures. DETAILED DESCRIPTION
[0025] The present invention is described in detail below with reference to the embodiments.
[0026] (Meth)acrylate monomers have the advantages of low viscosity, strong permeability, and low curing temperature, and are the preferred compounds for micropore plugging agents for graphite bipolar plates. Compared with acrylate compounds, methacrylate compounds are more susceptible to free radical thermal curing reactions, and the cured products have higher Tg (glass transition temperature), which means they have higher heat resistance. Therefore, most commercial micropore plugging agents use methacrylate monomers as the main component. However, after the polymerization of methacrylate monomers, few have a Tg exceeding 100°C, and their heat resistance is not as good as that of epoxy resin cured products. Also, because the cross-linking density is not high enough and they contain a large number of polar ester bonds, their resistance to ethylene glycol is not good enough.
[0027] The invention introduces a tetrafunctional monomer containing a methylsiloxane structure, which has high Tg and excellent ethylene glycol resistance.
[0028] The (meth) acrylated ring-opening compound of epoxycyclohexylethylcyclotetrasiloxane of the present invention is prepared by carrying out epoxy group ring-opening esterification reaction between epoxycyclohexylethylcyclotetrasiloxane and acrylic acid or methacrylic acid under the action of a catalyst, and after the reaction is completed, washing with water, alkali washing and water washing are performed for many times until the excess acrylic acid or methacrylic acid is completely washed away, and then drying and filtering are performed with a dehydrating agent to obtain a colorless and transparent acrylated ring-opening compound of epoxycyclohexylethylcyclotetrasiloxane or a methacrylated ring-opening compound of epoxycyclohexylethylcyclotetrasiloxane.
[0029] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0030] [Tetrafunctional silicone-1] Add 100g of epoxy cyclohexylethyl cyclotetrasiloxane to a four-necked glass reaction bottle with a Teflon stirring paddle, heat the oil bath to a liquid surface temperature of 80-90°C, and drop a mixture of methacrylic acid, triethylamine and BHT (the weights of the three are 15g, 1.0g, and 0.1g, respectively). After the addition is complete, control the reaction temperature to 110-120°C, maintain for 5 hours to stop the reaction, and cool to room temperature. The reactants are washed with water, alkali, and then washed with water several times until the excess methacrylic acid is completely washed away and the pH of the aqueous phase reaches neutrality. Then, dry and filter with a dehydrating agent to obtain a colorless and transparent methacrylated ring-opening compound of epoxy cyclohexylethyl cyclotetrasiloxane (referred to as tetrafunctional silicone-1).
[0031] [Tetrafunctional silicone-2] Add 100g of epoxy cyclohexylethyl cyclotetrasiloxane to a four-necked glass reaction bottle with a Teflon stirring paddle, heat the oil bath to a liquid surface temperature of 80-90°C, drop a mixture of acrylic acid, triphenylphosphine and MEHQ (the weights of the three are 12g, 1.0g, and 0.1g, respectively), and after the addition is complete, control the reaction temperature to 110-120°C, maintain for 5 hours to stop the reaction, and cool to room temperature. The reactants are washed with water, alkali, and then washed with water several times until the excess acrylic acid is completely washed away and the pH of the aqueous phase reaches neutrality, then dried and filtered with a dehydrating agent to obtain a colorless and transparent acrylated ring-opening compound of epoxy cyclohexylethyl cyclotetrasiloxane (referred to as tetrafunctional silicone-2).
[0032] The plugging agent formulation in each embodiment and comparative example is prepared by mixing the various components and stirring them evenly until the solid substances are dissolved into a transparent liquid.
[0033] The formulations of the embodiments and comparative examples are shown in Table 1 below.
[0034] Table 1
[0035]
[0036] The evaluation method for ethylene glycol resistance is as follows:
[0037] Pour 10g of the plugging agent into a Teflon mold with a diameter of 4.0cm and a height of 2.0cm, heat it in an 80℃ drying oven for 2h, then heat it to 120℃ and continue heating it for 2h to obtain a colorless and transparent cylindrical solid. Put the cylindrical solid into a glass bottle with 50%wt ethylene glycol aqueous solution and seal it, move it into a 90℃ oven and keep it for 1000h, take it out to examine the solubility of the solid and the turbidity of the ethylene glycol aqueous solution, so as to evaluate the ethylene glycol resistance of the plugging agent.
[0038] Ethylene glycol resistance is divided into 4 levels:
[0039] 1. Excellent◎ (the solidified material is intact, the ethylene glycol aqueous solution is transparent and free of foreign matter and turbidity)
[0040] 2. Good ○ (the solidified material has no obvious dissolution, and the ethylene glycol aqueous solution is slightly turbid)
[0041] 3. General △ (the solidified material is obviously dissolved, and the ethylene glycol aqueous solution becomes turbid)
[0042] 4. Very poor × (the solidified material swells and dissolves, and the ethylene glycol aqueous solution is slightly turbid)
[0043] According to Table 1, by comparing Example 1 and Comparative Example 1, it is found that the amount of tetrafunctional silicone added has a crucial influence on the ethylene glycol resistance. The tetrafunctional silicone added in an amount exceeding 20 phr (Parts per hundred) can achieve better resistance. When the tetrafunctional silicone added in an amount of 10 phr, the solidified material is obviously dissolved after aging, and the ethylene glycol aqueous solution becomes turbid. At the same time, the Tg of the obtained solidified material is relatively low, and the heat resistance is also poor.
[0044] The composition of Comparative Example 2 is all high-Tg methacrylate, and the Tg of the cured product is relatively high. However, because it does not contain an organic siloxane structure, its resistance to ethylene glycol is poor. After aging, the cured product swells and dissolves, and the ethylene glycol aqueous solution is slightly turbid.
[0045] The formula of Comparative Example 3 contains low-Tg difunctional acrylate, and the resulting cured product has a relatively low Tg, poor heat resistance, and relatively poor ethylene glycol resistance. After aging, the cured product swells and dissolves, and the ethylene glycol aqueous solution is also very turbid.
Claims
1. A flexible graphite bipolar plate micropore plugging agent with good heat resistance and ethylene glycol resistance, characterized in that: include: 20-40 parts by weight of (meth)acrylated ring-opening compound of epoxycyclohexylethylcyclotetrasiloxane and 60-80 parts by weight of high Tg methacrylate monomer, the total of which is 100 parts by weight, as well as 0.5-2 parts by weight of leveling agent and 0.2-1.0 parts by weight of free radical thermal initiator.
2. The plugging agent according to claim 1, characterized in that: The (meth) acrylated ring-opening compound of epoxycyclohexylethylcyclotetrasiloxane has the following structure: Here, R represents a methyl group or a hydrogen atom.
3. The plugging agent according to claim 1 or 2, characterized in that: The (meth) acrylic acid esterified ring-opening compound of epoxy cyclohexylethyl cyclotetrasiloxane is prepared by epoxy cyclohexylethyl cyclotetrasiloxane of formula I undergoing epoxy ring-opening esterification reaction with (meth) acrylic acid under the action of a catalyst and a free radical inhibitor:
4. The plugging agent according to claim 3, characterized in that: The catalyst is selected from tertiary amines and quaternary ammonium salts, and is commonly used as any one of triethylamine, N,N-dimethylbenzylamine, N,N-dimethylaniline, trimethylbenzylammonium chloride, triphenylphosphine, triphenylantimony, chromium acetylacetonate, chromium isooctanoate, organic tin compounds, and tetraethylammonium bromide, and its usage is 0.1% to 3% of the total mass of the reactants.
5. The plugging agent according to claim 3, characterized in that: The amount of (meth)acrylic acid added is 1.1 to 1.5 times the molar number of epoxy groups in epoxycyclohexylethylcyclotetrasiloxane.
6. The plugging agent according to claim 3, characterized in that: The free radical inhibitor is any one of p-methoxyphenol, hydroquinone, 2,5-dimethylhydroquinone and 2,6-di-tert-butyl-4-methylphenol, and the addition amount thereof is 0.01% to 1% of the total mass of the reactants.
7. The plugging agent according to claim 3, characterized in that: The specific reaction process is: heat epoxy cyclohexylethyl cyclotetrasiloxane to 80-90°C, add a mixture of (methyl) acrylic acid, a catalyst and a free radical inhibitor, and after the addition is completed, control the reaction temperature to 110-120°C, maintain this temperature for 5 hours, stop heating and cool to room temperature to obtain the target product.
8. The plugging agent according to claim 1, characterized in that: The high Tg methacrylate monomer is selected from any one of isobornyl (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, benzyl (meth)acrylate, phenyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, tetrahydrofuran methacrylate, tricyclodecyl (meth)acrylate, dicyclopentadiene (meth)acrylate, (meth)acryloylmorpholine and N,N-dimethylacrylamide, preferably isobornyl (meth)acrylate, dicyclopentadiene (meth)acrylate or tricyclodecyl methacrylate.
9. The plugging agent according to claim 1, characterized in that: The leveling agent is selected from any one of German BYK leveling agents BYK-333 and BYK-3505, and three positive polymer superdispersants CH-1, CH-2, CH-3, CH-5, CH-6, CH-7, CH-8, and CH-9.
10. The plugging agent according to claim 1, characterized in that: The free radical thermal initiator is an azo or peroxide free radical thermal initiator with a decomposition temperature of 80 to 95° C., preferably any one of azobisisobutyronitrile, azobisisoheptanenitrile or benzoyl peroxide.
Citation Information
Patent Citations
Resin mixture for preparing graphite bipolar plate as well as preparation method and application of resin mixture
CN116646547A
Textured graphite sheet infused with a sealant
WO2001043960A1
Improved monomer compositions for temperature resistance after curing
WO2023055587A1